2021
DOI: 10.3390/educsci11090543
|View full text |Cite
|
Sign up to set email alerts
|

Lessons in the Use of Technology for Science Education during COVID-19 Age under a Teachers’ Collaboration Cluster

Abstract: The COVID-19 confinement has represented both opportunities and losses for education. Rarely before has any other period moved the human spirit into such discipline or submission—depending on one’s personal and emotional points of view. Both extremes have been widely influenced by external factors on each individual’s life path. Education in the sciences and engineering has encountered more issues than other disciplines due to specialized mathematical handwriting, experimental demonstrations, abstract complexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…The differences in favor of the remote modality could be explained by the availability of the class session records and the students' positive perceptions of online material. These results are similar to the studies of Chhetri (2020), Potaliya andGhatak (2020), andDelgado et al (2021) who found that Medicine students preferred to watch several times the recorded classes for studying theoretical topics but attending face-to-face sessions for their practical subjects. Furthermore, remote classes have been reported to be the best way for continuous learning in ERT situations, as they promote engagement when students are autonomous, there are specific purposes in the activities, and there is interaction between professors and students (Binks et al, 2021;Yu-Fong Chang et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…The differences in favor of the remote modality could be explained by the availability of the class session records and the students' positive perceptions of online material. These results are similar to the studies of Chhetri (2020), Potaliya andGhatak (2020), andDelgado et al (2021) who found that Medicine students preferred to watch several times the recorded classes for studying theoretical topics but attending face-to-face sessions for their practical subjects. Furthermore, remote classes have been reported to be the best way for continuous learning in ERT situations, as they promote engagement when students are autonomous, there are specific purposes in the activities, and there is interaction between professors and students (Binks et al, 2021;Yu-Fong Chang et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…Evaluation can be conducted in all stages. The results of the evaluation provide important recommendations for the next decision-making or strategies to maintain, modify or improve what is no longer relevant (Attfield, 1999;Campbell-Patton, 2016;Chouinard & Cousins, 2009;Delgado et al, 2021;Lumino & Gambardella, 2020;Stufflebeam 2007).…”
Section: The Standardization Of Innovative Education In the Covid-19 Eramentioning
confidence: 99%
“…In addition to the overall technology used to forecast and manage online courses, many applications have been deployed to share, deliver, and receive educative materials, integrating services not always included in a unique service. More critical, concrete applications were used to supersede the absence of experimental practices, including simulators and smartphone applications that integrated sensors for straightforward physical measurements to set up experiments [7,16]. Despite the limitations, the effective use of such technologies produced changes in each student, who acquired new competencies to approach the learning of physics concepts.…”
Section: Teaching Physics During the Covid-19 Pandemicmentioning
confidence: 99%
“…In addition, using a scientific calculator on a smartphone shared on the screen and some other elements easing visualization (such as Mathematica, Matlab, and Desmos) promoted an enriched learning experience (traditionally absent in the pre-pandemic approach, but now inherited in the 'New Normal' practice). The complementary series of teaching videos solving additional physics problems was published on the Learning Management System (LMS), commonly used by the institution in the form of a virtual classroom (which is now included in the new face-to-face course version in the 'New Normal' period) [7,15]. We wanted to analyze student transitions through the different stages of the COVID-19 pandemic and consider the teacher learning inherited from the online teaching experience.…”
Section: Physics For Computer Science and Programming Related Programsmentioning
confidence: 99%
See 1 more Smart Citation